Methods in proteome and protein analysis - Kamp, Roza Maria Calvete, Juan J (Springer-Verlag, 2004)
'Methods in Proteome and Protein Analysis' presents the most interesting papers from the 14th MPSA meeting, including those on mass spectrometry for protein research, protein-protein interaction using MALDI-MS, and the classification and prediction of structure or functional sites.